NERACA NITROGEN KAMBING PERANAKAN ETAWA YANG DIBERIKAN TINGKAT KONSENTRAT DAN HIJAUAN BERBEDA - Anak Agung Ngurah Badung Sarmuda Dinata; Sentana Putra (Pusbindiklat - LIPI, 2014)
The research was conducted to determine the nitrogen balance in etawa descendant goat (PE) that is fed at different levels of concentrate and forage diets. Nine PE goats with average body weight of 23,98 ± 3,18 kg were used in this research for three months. This study was arranged in a completely randomized block design with 3 treatments and three blocks as replications. Treatments were PE goats fed 55% forage diets (Pennisetum purpureum) + 45% consentrate (A) ; PE goats fed 70% forage diets (P. purpureum: Gliciridia sepium = 2 : 3) + 30% concentrate (B) ; and PE goats fed 85% forage diets (P. purpureum: G. sepium : Hibiscus tilliacius = 1: 3 :1) +15% concentrate (C). Parameters of N intake, N digestible, N retention, biological value and net nitrogen utilization were observed. The result indicated that C treatment was the best of nitrogen balance with nitrogen retention was 14,5 g/d. This result was consistent with the highest dry mater intake of treatment C. This study suggests that PE goats which are given treatment C resulted the best nirogen balance.